Sustainability of entrepreneurship in handcrafted Nigerian products: a case study of North Western States - Muhammad, Abubakar; Zakari, Y. A. (Journal of Social Review and Development, 2025)
This study investigates the sustainability of entrepreneurship in handcrafted Nigerian items, concentrating on the North Western states of Kano, Kaduna, Katsina, Jigawa, Kebbi, Sokoto, and Zamfara. Utilising secondary data from scholarly literature, governmental papers, and digital platforms, alongside focused primary data from artisan interviews, the study assesses the economic, social, and environmental aspects of sustainability. The results show that crafts like textiles, leatherwork, and pottery can help the economy, but they also face problems including not being able to go to markets, not having enough infrastructure, and competition from imports. These businesses protect cultural heritage and provide communities power in social terms. In environmental terms, they use local materials but are at risk of using too many resources. Primary data enhances these insights by disclosing artisans' viewpoints on operational impediments and innovation requirements. The report suggests ways to make things more sustainable, such as forming cooperatives, using internet marketing, and using eco-friendly methods. This research aligns with Sustainable Development Goals and highlights the potential of artisanal entrepreneurship to cultivate resilient economies, providing recommendations for policymakers and stakeholders to bolster this sector.